THE NEEDS OF CLEAN WATER STUDY IN SOUTH BARITO REGENCY - Sofia, Elma; Permana, Hendra Bangkit; Fitriati, Ulfa (INFO-TEKNIK, 2020)
South Barito Regency is one of the regencies in province of Central Kalimantan. South Barito Regency is a regency whose developing quite rapid because in terms of its geographical location, South Barito Regency passed by national road and become a place of transit which also led to an increase in population and economic needs, especially the need for clean water. There are still areas experiencing water shortage problems because of the difficulty of distributing clean water. The purpose of this study was to determine the amount of water needs for 2017, 2021, 2026, 2031, and 2036 to serve the needs of community and also determine the water quality at the intake, and comparing water demand with intake capacity. In this study, the calculation of population projections using statistical methods in which to pay attention to the rate of population growth of the past to estimate the number of people in the future. There are several methods that can be used to analyze the population growth in the future, namely arithmetic, geometric, linear regression, exponential, and logarithmic. For water quality check, field survey is needed to test parameters such as temperature, electrical conductivity, the amount of dissolved solids, pH, turbidity, salinity, and dissolved oxygen measurements. Results of this research is needed clean water discharge Barito Selatan with consecutive results as follows in 2017; 2021; 2026; 2031; In 2036 amounted to 305.14 L / s, 429.55 L / s, 599.58 L / s, 755.02 L / s, 794.94 L / s .With intake capacity which is now only 184.5 L / s, it can be said that the need for clean water unfulfilled. In the aspect of water quality, source of raw water used by Water Supply Company of South Barito has not meet the standards in terms of pH and turbidity, so the use of water is not safe for the people of South Barito Regency.